2022
DOI: 10.2196/39954
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Usability of eHealth Solutions for Patients With Parkinson Disease: Observational Study

Abstract: Background Parkinson disease (PD) is a neurodegenerative disorder with a variety of motor and nonmotor symptoms. Many of these symptoms can be monitored by eHealth solutions, including smartphone apps, wearable sensors, and camera systems. The usability of such systems is a key factor in long-term use, but not much is known about the predictors of successful use and preferable methods to assess usability in patients with PD. Objective This study tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…In a separate qualitative study, individuals with PD identified wearable device design (e.g., need for battery replacement) as a potential barrier to use [68]. In another study, usability of a camera system was influenced by age and motor impairment while the usability of a tablet-based application was influenced by cognitive status and digital health literacy [69]. These results need to be interpreted with caution as individuals who participate in such studies are a self-selected group likely to have more familiarity with digital health technologies than the general PD population.…”
Section: Wearables and Smartphone Applicationsmentioning
confidence: 99%
“…In a separate qualitative study, individuals with PD identified wearable device design (e.g., need for battery replacement) as a potential barrier to use [68]. In another study, usability of a camera system was influenced by age and motor impairment while the usability of a tablet-based application was influenced by cognitive status and digital health literacy [69]. These results need to be interpreted with caution as individuals who participate in such studies are a self-selected group likely to have more familiarity with digital health technologies than the general PD population.…”
Section: Wearables and Smartphone Applicationsmentioning
confidence: 99%
“…Bendig et al [17] performed comprehensive usability assessments with 18 patients with Parkinson's disease using a mixed-methods usability battery containing the system usability scale, a rater-based evaluation of device-specific tasks, and qualitative interviews.…”
Section: Related Workmentioning
confidence: 99%